A sodium polyacrylate modified bentonite impermeable material for barrier containment and a method of making the same
Patent Information
- Application Number
- CN202410238347.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-03
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-03-03
AI Technical Summary
[0005]本发明拟解决的技术问题是:为解决污染物在地层流体作用下的渗流污染问题,改善高性能防渗屏障用膨润土长期依赖进口的不利局势,基于优选后的国产钠基膨润土材料,利用聚丙烯酸钠对其渗流和渗透性能进行了改性处理,制备了渗透系数降低至10-12 m/s数量级的高性能污染场地的防渗材料
[0012]本发明研发了一种新的防渗材料及其制备方法,其中聚丙烯酸钠质量占膨润土的质量比为10%,当与地下流体中的水接触水化反应后,材料的流动阻力大幅增加,再加上聚丙烯酸钠对膨润土的孔隙填充作用,显著地减少了地层流体的可用流动空间,同时增加了渗流孔隙的迂曲度,其作用结果是聚丙烯酸钠改性膨润土防渗材料的渗透系数k大幅降低,至10-12 m/s数量级,远低于其它屏障材料,且在剧烈水流流过时粘度值显著下降(采用转速模拟)。一方面,使用聚丙烯酸钠对膨润土进行共混改性处理,孔隙填充作用减少了地层流体的可用流动空间,同时增加了渗流孔隙的迂曲度,聚丙烯酸钠在地层水的作用下吸水膨胀,膨润土在改性土的表面形成液膜/水化泥皮,防止地层水与膨润土进一步接触和离子交换反应,增强了膨润土的防渗性能;同时,聚丙烯酸钠对膨润土的孔隙填充作用和对膨润土片的剥离,进一步增强了聚丙烯酸钠-膨润土复合材料的防渗性能。
Smart Images

Figure CN118324454B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental geotechnical engineering technology, specifically relating to a sodium polyacrylate modified bentonite impermeable material for barrier barrier and its preparation method, as well as application examples of the impermeable material prepared based on the method. Background Technology
[0002] Bentonite is widely used as an impermeable material for contaminated sites due to its low permeability and adsorption capacity. However, studies have found that when bentonite is used as an impermeable material, under conditions of high precipitation or corrosive leachate, high-valence metal ions replace the exchangeable cations between the bentonite layers, compressing the bentonite double electric layer. This increases the interlayer gaps, allowing water to flow between particles, increasing the permeability coefficient by several orders of magnitude, and significantly deteriorating the impermeability, thus failing to meet the impermeability requirements of antifouling barriers.
[0003] Currently, polymer-modified soil materials exhibit problems such as polymer chain breakage, low polymer crosslinking / grafting rates, poor polymer-bentonite bonding strength, and dissolution under acid-base / salt / dry-wet cycling conditions in corrosive liquid or wet-dry environments. Therefore, improving the impermeability of polymer-modified soils in mining / corrosive environments, enhancing their chemical structural stability, and strengthening the impermeability of barrier materials are crucial for reducing material cracking during wet-dry cycling and extending the service life of antifouling barriers.
[0004] Furthermore, to prevent the seepage and diffusion of contaminated liquids in the strata, polymer-modified soil, as a pollution barrier material, needs to form a physical barrier structure to confine the leachate within a certain space of soil pores. This places high demands on the physical barrier effect of the barrier material. In particular, in contaminated sites with high precipitation or corrosive leachate environments, the richer surface / stratum fluid exchange places even higher demands on the impermeability of the barrier material. When contaminated leachate comes into contact with the barrier material, the polymer-modified soil material needs to have an extremely low permeability coefficient to minimize the diffusion of contaminated liquids to the surrounding area. Current technology has not yet found a permeability coefficient reaching 10. -12 Modified soil with a viscosity on the order of m / s and a significant decrease in viscosity when subjected to strong water flow. Summary of the Invention
[0005] The technical problem this invention aims to solve is: to address the seepage pollution problem caused by formation fluids and to improve the unfavorable situation of long-term reliance on imported bentonite for high-performance seepage barriers, this invention, based on optimized domestic sodium-based bentonite materials, modifies its seepage and permeability properties using sodium polyacrylate, resulting in a material with a permeability coefficient reduced to 10. -12This invention provides a high-performance seepage barrier material for contaminated sites with a permeability coefficient on the order of m / s. Compared to similar polymer-modified bentonite, the sodium polyacrylate-modified bentonite seepage barrier material provided by this invention exhibits a significantly higher reduction in permeability coefficient, along with a substantial reduction in formulation costs. Its anti-seepage performance has reached a leading level in China.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: This invention provides a sodium polyacrylate-modified bentonite impermeable material for barrier purposes. The polymer-modified bentonite material comprises bentonite and sodium polyacrylate. In preparing the impermeable material, deionized water is used as a solvent, and the mass of added sodium polyacrylate is 10% of the mass of bentonite. The molecular weight of the sodium polyacrylate is 8 × 10⁻⁶. 6 The bentonite added is at a mass of g / mol, which is 10% of the mass of the deionized water, and the bentonite has a particle size of less than 0.075 mm. The impermeable material is mixed with water at a weight of 10 times its weight to obtain a pre-hydration slurry. After hydration for 24 hours, a post-hydration slurry is obtained. The viscosity of the post-hydration slurry at 6 r / min is 1.3 to 1.4 times that of the pre-hydration slurry at 6 r / min, and the viscosity of the post-hydration slurry at 6 r / min is 8 to 10 times, preferably 9 to 10 times, and preferably 9.3 times, its viscosity at 60 r / min is greater than its viscosity at 60 r / min. The permeability coefficient of the impermeable material, as measured by the improved filtration loss test, is less than 9 × 10⁻⁶. -12 m / s.
[0007] On the other hand, this application provides a method for preparing the above-mentioned sodium polyacrylate modified bentonite impermeable material for barrier barrier purposes, comprising the following steps: Step 1: Heat deionized water to 70°C in a constant temperature oil bath, add sodium polyacrylate, and stir at a constant temperature of 70°C to obtain a sodium polyacrylate solution. The mass of sodium polyacrylate in the solution accounts for 10% of the mass of bentonite. The purpose of the constant temperature 70°C oil bath is to promote the dissolution of the polymer in the deionized water. The purpose of dissolving the polymer at a constant temperature is to make it mix better with bentonite. Experiments have selected 70°C as the optimal temperature in the constant temperature oil bath.
[0008] Step 2: Under constant temperature oil bath conditions of 70℃, add bentonite to sodium polyacrylate solution. The mass of added bentonite accounts for 10% of the mass of deionized water. Stir at a uniform speed. After the reaction, a sodium polyacrylate-bentonite mixed slurry is formed. If the amount of bentonite added is too low, the modification efficiency will decrease, leading to increased costs; if the amount of bentonite added is too high, it may cause insufficient hydration of the clay flakes. Experiments have shown that 10% is the optimal amount. In step 2, the purpose of dissolving the bentonite at a constant temperature is to better mix it with the bentonite; experiments have shown that 70℃ is the optimal temperature in the constant temperature oil bath.
[0009] Step 3: Dry the sodium polyacrylate-bentonite mixed slurry at 105℃ to constant weight, grind it, and pass it through a 200-mesh standard sieve to obtain sodium polyacrylate modified bentonite seepage-proof material.
[0010] Preferably, in step 1, the stirring speed is 2000 r / min and the stirring time is 90 min. Too low a stirring speed or too short a stirring time will affect the dissolution and dispersion of sodium polyacrylate; too high a stirring speed or too long a stirring time may cause mechanical decomposition of the sodium polyacrylate molecular structure, thereby affecting the reaction efficiency and dissolution effect. In step 2, the stirring speed is 2000 r / min and the stirring time is 120 min. Too low a stirring speed or too short a stirring time will affect the dispersion and reaction rate of sodium polyacrylate-bentonite; too high a stirring speed or too long a stirring time may cause mechanical decomposition of the sodium polyacrylate-bentonite structure, thereby affecting the reaction efficiency and impermeability.
[0011] The present invention also provides an application of the above-mentioned seepage-proof material, wherein the seepage-proof material is dissolved in 10 times its weight of water and left to stand for 24 hours, and then used for barrier construction.
[0012] This invention develops a novel seepage-proof material and its preparation method, wherein sodium polyacrylate accounts for 10% of the mass of bentonite. Upon contact with water in underground fluids and undergoing a hydration reaction, the material's flow resistance increases significantly. Furthermore, the pore-filling effect of sodium polyacrylate on bentonite significantly reduces the available flow space for formation fluids and increases the tortuosity of the seepage pores. As a result, the permeability coefficient k of the sodium polyacrylate-modified bentonite seepage-proof material is significantly reduced to 10. -12 The viscosity is on the order of m / s, far lower than other barrier materials, and the viscosity value decreases significantly when subjected to intense water flow (simulated using rotational speed). On one hand, the use of sodium polyacrylate to modify bentonite reduces the available flow space for formation fluids by filling pores, while increasing the tortuosity of the seepage pores. Sodium polyacrylate absorbs water and expands under the action of formation water, and bentonite forms a liquid film / hydrated mud cake on the surface of the modified soil, preventing further contact and ion exchange reactions between formation water and bentonite, thus enhancing the seepage prevention performance of bentonite. At the same time, the pore-filling effect of sodium polyacrylate on bentonite and the peeling of bentonite flakes further enhance the seepage prevention performance of the sodium polyacrylate-bentonite composite material.
[0013] The process parameters of this invention effectively enhance the seepage prevention capability of sodium polyacrylate-modified bentonite barrier materials, forming a barrier against pollutants. The permeability coefficient of the resulting sodium polyacrylate-modified bentonite barrier material is far lower than the seepage prevention requirements of bentonite barrier materials. Furthermore, the processing steps are simple, energy consumption is low, and industrial production costs are significantly reduced, facilitating mass production and application. Therefore, the polymer material provided in this invention has broad prospects for industrial production and application. Attached Figure Description
[0014] Figure 1 This is a flowchart illustrating the overall process for preparing a sodium polyacrylate-modified bentonite impermeable material for barrier purposes according to the present invention. Figure 2 The viscosity of the slurry of sodium polyacrylate modified bentonite impermeable material before and after hydration; Figure 3 Viscosity of the polymer-modified soil slurry used in the implementation case (viscosity values of four mass concentrations of polymer-modified soil slurry under two working conditions and four shear speeds). Figure 4 This table shows the impermeability coefficients of the sodium polyacrylate-modified bentonite impermeable material for barrier purposes under different polymer dosages according to the present invention. Detailed Implementation
[0015] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. However, it should be noted that the embodiments described herein are not intended to limit the invention. Equivalent modifications or substitutions in test functions, test methods, or equipment structures made by those skilled in the art based on these embodiments are all within the scope of protection of the present invention. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of the present invention.
[0016] To verify the good performance of the sodium polyacrylate modified bentonite impermeable material for barrier barrier of the present invention, the present invention further describes the sodium polyacrylate modified bentonite impermeable material for barrier barrier and its preparation method. The present invention specifically implemented the sample preparation work of the impermeable material, which was verified as an example. Example
[0017] Step (1): Heat the deionized water to 70°C; In step 10), deionized water is used as a solvent to dissolve sodium polyacrylate, and the constant temperature of 70°C is used to promote the dissolution of the polymer.
[0018] Step (2): Under constant temperature oil bath conditions of 70℃, sodium polyacrylate and deionized water are mixed and stirred at a constant temperature and speed to obtain sodium polyacrylate solution. In step (2), sodium polyacrylate is prepared at a mass ratio of 10% to bentonite; In step (2), sodium polyacrylate and water are stirred using a mixer at a speed of 2000 r / min for 90 min.
[0019] Step (3): Under constant temperature oil bath conditions of 70℃, add bentonite to sodium polyacrylate solution and stir at a uniform speed so that sodium polyacrylate can fill the pores between bentonite layers and peel off the bentonite sheets. After the reaction, a uniform sodium polyacrylate-bentonite mixed slurry is formed. In step (3), the mass of bentonite in the sodium polyacrylate-bentonite mixed slurry accounts for 10% of the mass of the prepared water; In step (3), the sodium polyacrylate-bentonite mixture is stirred using a mixer under a constant temperature oil bath of 70°C. The mixer speed is 2000 r / min and the stirring time is 120 min.
[0020] Step (4): The sodium polyacrylate-bentonite mixed slurry is dried, ground, and sieved to obtain sodium polyacrylate modified bentonite impermeable material; In step (4), the sodium polyacrylate-bentonite mixed slurry is dried in a drying oven at a temperature of 105°C until constant weight is obtained, thus obtaining sodium polyacrylate modified bentonite solid. In step (4), the sodium polyacrylate modified bentonite solid is ground using a grinder and then passed through a 200-mesh standard sieve to obtain the sodium polyacrylate modified bentonite seepage-proof material. Example
[0021] The following experiments were conducted on the impermeable material obtained in Example 1: Weigh out 500 ml of deionized water as the water for the sodium polyacrylate bentonite hydration slurry to be prepared. Weigh out 15 g, 25 g and 50 g of sodium polyacrylate modified bentonite seepage prevention material respectively (the mass fractions of which are 3%, 5% and 10% of water respectively). At room temperature, the sodium polyacrylate modified bentonite impermeable material is uniformly added to water under the condition of stirring at a constant speed using a mixer, so that it is fully dissolved and hydrated to obtain sodium polyacrylate bentonite hydrated slurry. The mixer speed was 2000 r, the mixing time was 15 min, and the resulting sodium polyacrylate bentonite slurry before hydration was recorded as samples ①, ②, ③ and ④, respectively. Using a rotational viscometer, the viscosity values of deionized water, 3%, 5%, and 10% sodium polyacrylate bentonite hydrated slurries were measured under different rotational speeds before and after 24 hours of hydration. Among them, the viscosity of sodium polyacrylate bentonite hydration slurry was measured by a rotational viscometer at rotational speeds of 6 r / min, 12 r / min, 30 r / min and 60 r / min.
[0022] The viscosity values measured in the examples of this invention are as follows: Figure 3 As shown.
[0023] As the rotational viscometer rotor speed increases (increasing shear rate), the viscosity of the sodium polyacrylate-modified bentonite slurry decreases, indicating that the slurry exhibits shear dilution and its flow behavior conforms to pseudoplastic flow laws. When the mass concentration of the sodium polyacrylate-modified bentonite slurry is 0%, 3%, 5%, and 10%, the rotational viscosity of the slurry increases significantly with increasing mass concentration before and after 24 hours of hydration, with a more significant increase after 24 hours. This indicates that after the sodium polyacrylate-modified bentonite slurry comes into contact with water in the underground fluid, the flow resistance of the material increases significantly. Furthermore, the pore-filling effect of sodium polyacrylate on bentonite significantly reduces the available flow space for formation fluids and increases the tortuosity of the seepage pores. The result is a significant decrease in the permeability coefficient (k) of the sodium polyacrylate-modified bentonite slurry.
[0024] The sodium polyacrylate-modified bentonite seepage barrier material provided by this invention, upon contact with formation fluids or leachate, forms a hydrated mud cake on the surface of the barrier, effectively preventing further intrusion of contaminated fluids and extending the service life of the barrier while providing a barrier function. Based on the test results of steps 50)-80) of this invention, the 10% addition of sodium polyacrylate-modified bentonite seepage barrier material meets the above seepage prevention requirements; therefore, a 10% addition is selected as the optimal formulation for the preferred test.
[0025] Comparative Example 1 The difference between this application and the present application lies in the order of addition of bentonite and sodium polyacrylate: bentonite is first dissolved in deionized water and stirred evenly, then sodium polyacrylate is added. The remaining formulation and operation method are the same as in this application, resulting in comparative material 1. The permeability coefficient k-value was evaluated using an improved filtration loss test. The permeability coefficient of comparative material 1 only reached 10. -10 On the order of m / s.
[0026] Comparative Example 2 Four parallel samples were prepared using the same method as in Example 1, except that the amount of sodium polyacrylate added was 0% (Comparative Material 2), 2% (Comparative Material 3), 5% (Comparative Material 4), and 10% of the bentonite content, respectively. The polypropylene permeability coefficient k-value was evaluated using a modified filtration loss test. The permeability coefficient showed a decreasing trend with increasing polymer content, reaching a minimum of 10. -12 The permeability coefficient values measured in the examples of this invention are on the order of m / s. Figure 4 As shown.
[0027] Comparative Example 3 The preparation method is the same as in Example 1, except that the amount of sodium polyacrylate added is 15% of the bentonite content, resulting in Comparative Material 5.
[0028] The experiments described in Example 2 were conducted on comparative materials 1-5. The test results showed that the impermeable material obtained according to the preparation steps and preparation addition ratio (10%) of the present invention showed the most significant decrease in viscosity value after dissolution with the increase of rotation speed (wherein, the optimal amount of water is 10 times the weight of the impermeable material for dissolution, and the viscosity value of the slurry at 6 r / min after hydration is 9 to 10 times that at 60 r / min).
[0029] The permeability coefficient of the sodium polyacrylate modified bentonite seepage barrier material of the present invention is much lower than that of bentonite barrier material; moreover, the processing steps of the sodium polyacrylate modified bentonite seepage barrier material are simple, the energy consumption is low, and the industrial production cost is significantly reduced.
Claims
1. A sodium polyacrylate-modified bentonite impermeable material for barrier sealing, the impermeable material comprising bentonite and sodium polyacrylate, characterized in that, In preparing the impermeable material, deionized water is used as the solvent, and the mass of added sodium polyacrylate is 10% of the mass of bentonite. The molecular weight of the sodium polyacrylate is 8 × 10⁻⁶. 6 The bentonite content is g / mol, and the mass of the added bentonite is 10% of the mass of the deionized water. The particle size of the bentonite is less than 0.075 mm. The preparation method of the impermeable material includes the following steps: Step 1: Heat deionized water to 70°C in a constant temperature oil bath, add sodium polyacrylate, and stir at a constant temperature of 70°C to obtain a sodium polyacrylate solution. The mass of sodium polyacrylate in the solution is 10% of the mass of bentonite. Step 2: Under constant temperature oil bath conditions of 70℃, add bentonite to sodium polyacrylate solution. The mass of added bentonite accounts for 10% of the mass of deionized water. Stir at a uniform speed. After the reaction, a sodium polyacrylate-bentonite mixed slurry is formed. Step 3: Dry the sodium polyacrylate-bentonite mixed slurry at 105℃ to constant weight, grind it, and pass it through a 200-mesh standard sieve to obtain sodium polyacrylate modified bentonite seepage-proof material.
2. A method for preparing the impermeable material according to claim 1, characterized in that, Includes the following steps: Step 1: Heat deionized water to 70°C in a constant temperature oil bath, add sodium polyacrylate, and stir at a constant temperature of 70°C to obtain a sodium polyacrylate solution. The mass of sodium polyacrylate in the solution is 10% of the mass of bentonite. Step 2: Under constant temperature oil bath conditions of 70℃, add bentonite to sodium polyacrylate solution. The mass of added bentonite accounts for 10% of the mass of deionized water. Stir at a uniform speed. After the reaction, a sodium polyacrylate-bentonite mixed slurry is formed. Step 3: Dry the sodium polyacrylate-bentonite mixed slurry at 105℃ to constant weight, grind it, and pass it through a 200-mesh standard sieve to obtain sodium polyacrylate modified bentonite seepage-proof material.
3. The preparation method according to claim 2, characterized in that, In step 1, the stirring speed is 2000 r / min and the stirring time is 90 min; in step 2, the stirring speed is 2000 r / min and the stirring time is 120 min.
4. The application of the impermeable material according to claim 1 in barrier construction, characterized in that, Mix the impermeable material with water of 10 times its mass and let it stand for 24 hours, then use it for barrier construction.
Citation Information
Patent Citations
Organic pollutant-resistant polymer bentonite nanocomposite material and preparation method thereof
CN105199288A